EFFECT OF EMOTIONAL INTELLIGENCE AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF STATE CIVIL SERVANTS AT THE OFFICE OF WOMEN'S EMPOWERMENT, CHILD PROTECTION, POPULATION CONTROL AND FAMILY PLANNING, PASAMAN REGENCY - Yurasti Yurasti; Ria Widhia Sari; Afridawati Afridawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study was conducted to assess the impact of emotional intelligence and organizational culture on the job performance of civil officials at the regional office of Women's Empowerment, Child Protection, Population Control, and Family Planning in Pasaman Regency. This study's sample consisted of 49 respondents. Multiple linear regression was utilized to evaluate this study's data. The results indicated that emotional intelligence had a substantial impact on the job performance of government officials at the regional office of Women's Empowerment, Child Protection, Population Control, and Family Planning in Pasaman Regency, with a significant value of 0.000 alpha = 0.05. With a significant value of 0.049 alpha 0.05, organizational culture had a marginally significant effect on the job performance of government servants at the Regional Office of Women’s Empowerment, Child Protection, Population Control and Family Planning of Pasaman Regency. The significant value of 0.00 alpha 0.05 indicates that both emotional intelligence and organizational culture had a significant impact on performance concurrently. According to the results of the coefficient of determination test, emotional intelligence and organizational culture account for 51% of government workers' job performance.